Filipino Work Values and Job Satisfaction among School Heads of Selected Elementary Schools in the Division of Zambales - Laurenio Jr, Welmer A.; Cabal, Esmen M. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
nderstanding work values and their impact on career behavior is crucial in organizational settings. This study aimed to investigate Filipino work values among school heads in selected elementary schools in the Division of Zambales and its relationship to job satisfaction. Utilizing survey questionnaires, data was collected from school head-respondents to assess their work values and job satisfaction levels. Result showed that Filipino work values were rated as highly important by the school head-respondents, and overall job satisfaction was reported to be high. Significant differences in Filipino work values were observed based on various factors. Specifically, environmental work values varied significantly when grouped according to monthly income, familial work values varied significantly based on position/designation and monthly income, and organizational work values differed significantly when grouped according to sex. However, no significant differences in job satisfaction were found when school head-respondents were grouped based on profile variables such as job security, work environment, job responsibilities, and community linkages/attachments. Based on these findings, it is recommended that the Human Resource Management (HRM) Office may consider thorough evaluation of work values prior to promotion of employees. Furthermore, future researchers may conduct further studies on the strategies on Filipino work values and job satisfaction among school heads involving a wider scope of sample and research locale to validate the findings obtained from this study. Understanding and promoting Filipino work values can lead to a more fulfilled and effective school leadership, ultimately benefiting the educational environment and overall school performance.